Pengawasan E Commerce Dalam Undang-Undang Perdagangan Dan Undang-Undang Perlindungan Konsumen - Pariadi, Deky (UI Scholars Hub, 2018)
E-commerce started to expand significantly when the internet was introduced. Internet makes trade transactions no longer sees the boundaries of the country. The number of ease in accessing the internet makes consumer of e-commerce increased, some of the reasons, among others, is a practical, easy payment systems, efficiency of time and the many attractive promo price of online businesses. But reversed all the convenience and benefits offered, also arises concerns about online corporate responsibility to the consumer e-commerce because so many companies online. Act No. 7 of 2014 on Trade (Commerce Act) and Law No. 8 of 1999 on Consumer Protection (Consumer Protection Act) as a reference for every business in trade transactions, both conventional trade and e-commerce. Implementation of e-commerce transactions are growing rapidly to be balanced with strict supervision from government in every implementation.